Gun Violence Prevention? The Politics Behind Policy Responses to School Shootings in the United States - E. M. Kerr, Selina (Springer International Publishing, 2018)
This book examines the gun-related policy responses to three school shooting incidents in the United States. Gun violence prevention activists and others involved in policy making were interviewed for the book, and news media articles and policy documents were critically assessed. As a result, interpretations of the Second Amendment are shown to affect the acceptability of certain gun restrictions. News media content and policy documents, coupled with the thoughts of activists, also give an indication of why certain policy measures passed and others failed at the time of each of the case studies. This book should be of interest to social policy, politics, criminology and sociology students and academics, as well as those with a general interest in the topic.